واقع الأداء التنافسي في الصناعة المصرفية الجزائرية للفترة (2021-2012) - زروق رقية; مفتاح صالح (جامعة الوادي University of Eloued, 2024)
هدفت الدراسة إلى التعرف على واقع الأداء التنافسي في الصناعة المصرفية الجزائرية، بالتعرف على تنافسية المؤسسات المصرفية الجزائرية وأدائها التنافسي خلال الفترة (2021-2012) من خلال التطرق إلى مؤشرات الأداء التنافسي والتي تتمحور حول قياس الأداء المتعلق بالربحية ومؤشر يتعلق بالأداء السوقي مقارنة بالمنافسين مثل الحصة السوقية، ومؤشرات تتعلق بالابتكار كعدد المنتجات والخدمات الجديدة المقدمة، والأداء المتعلق بقيادة التكلفة مثل القدرة على تقديم منتجات وخدمات بأسعار تنافسيةـ، وتوصلت الدراسة إلى محدودية ممارسة المنافسة في القطاع المصرفي الجزائري مما يستدعي توفیر أكبر قدر ممكن من شروط المنافسة، على اعتبار ان تشجیع سیطرة البنوك العمومیة على الصناعة المصرفیة في الجزائر سیبقي على ضعف استخدام موارد تلك البنوك العمومیة مقارنة بالبنوك الخاصة، وهذا ما جعل البنوك الخاصة احسن أداء من البنوك العمومية، وكذا ضرورة تطویر التكنولوجیا المستخدمة في تقدیم الخدمات المصرفیة، والتي بإمكانها العمل على تحسین هیكل تكالیف البنوك. The study aimed to identify the reality of competitive performance in the Algerian banking industry, by identifying the competitiveness of Algerian banking institutions and their competitive performance during the period (2012-2021) by addressing competitive performance indicators, which revolve around measuring performance related to profitability and an indicator related to market performance compared to competitors such as market share, and indicators related to innovation such as the number of new products and services provided, and performance related to cost leadership such as the ability to provide products and services at competitive prices. Practicing competition in the Algerian banking sector, which requires providing the largest possible amount of competition conditions, considering that encouraging public banks to control the banking industry in Algeria will maintain the weak use of the resources of these public banks compared to private banks, and this is what made private banks better performing than public banks, as well as the need to develop the technology used in providing banking services, which can work to improve the structure of banks' costs.
The reality of competitive performance in the Algerian banking industry for the period (2012-2021)
Keywords: اداء تنافسي; صناعة مصرفية; : performance; competitiveness; market share; competitive performance; banking industry